PSYCHOSOCIAL FACTORS AND CONDITIONS ASSOCIATED WITH THE NON-ORGANIC FAILURE TO THRIVE IN INFANTS AND YOUNG CHILDREN - CARMEN COSTEA-BĂRLUȚIU (Studia Universitatis Babes-Bolyai, 2010)
ABSTRACT. Non-organic failure to thrive in infants and young children is a severe condition with a strong impact on the child's developmental outcomes. We analyzed social environmental, emotional, behavioral and temperamental factors, as well as several mental health issues drawn from observation and assessment of sixty-nine infants and toddlers hospitalized for nutrition disorders, in order to determine the impact of non-organic FTT on the child's development at this stage. Several implications for enhancement of resilience were also derived.